ஊடகங்களின் சுயகட்டுப்பாடு - Raguram, S. (Department of Government Information, Ministry of Information, Government of Sri Lanka and University of Kelaniya, 2013)
Media Freedom is one of the widely discussed topics in the contemporary world. The strength of Democracy in any country is determined through the free functioning of media. Media Freedom is often seen as an indicator to measure the strength of democratic governance. In this way, media freedom and democratic values are interconnected with each other. Freedom of expression is legally recognized in every country. The various international legal instruments including United Nations’ conventions and global Human Rights declarations give utmost importance to freedom of speech to ensure that it is protected with utmost importance. Further, media freedom is considered as one of the Human Rights. At the same time, the definition of media freedom not only covers the freedom of media institutions but is also viewed as an expression of individual freedom. Human rights activists view these two aspects are directly connected. This phenomenon increases the importance of media freedom. However, in reality, there are questions that remain unanswered are: to what extent media freedom is exercised and freedom of expression enjoyed by media organizations. Media freedom remains an important identity symbol of democracy. Even though, media organizations face a severe battle to obtain the honourable and respectful place that they deserve. Media freedom is continuously undermined by violations and violence unleashed against journalists and media entities. The respect for the freedom of expression in the contemporary and tolerance over the alternative opinions are visibly declining. Very often, contemporary society does not dare to challenge an opinion with an alternative opinion. This situation makes the existence of media freedom very difficult. In this situation, the media organizations and journalists are left with no option but to struggle for media freedom. As pointed out earlier, the enjoyment of individual freedoms is only possible in societies where media freedom is given the highest value and protection. When the community realizes this reality, the civil society and the general public will go hand in hand with media organizations and journalists in the struggle for media freedom. This is the way to protect democracy through media. It is a generally acknowledged fact that when we talk about freedom we must concentrate more on the limits of freedom. Then only the freedom we enjoy will not affect the freedom of others. In this backdrop, the Media Self-Regulation reiterates the way of defining media freedom by media organizations.